Evaluating Housing Quality, Energy Performance, Indoor Environment, and User Satisfaction in Renovated Locked-In Owner-Occupied Homes in Belgium - Leontien Bielen; Katleen Van den Broeck; Alexis Versele; Hilde Breesch (Buildings)
Approximately 3% of home-owners in Flanders (Belgium) are “locked-in”, residing in substandard dwellings with limited financial means for improvement. Under the European Urban Innovative Actions project ICCARus, 84 dwellings of locked-in home-owners in Ghent (Belgium) underwent renovations with an average budget of EUR 29,000. Their impact on housing quality, energy performance, indoor environmental quality (IEQ), and user satisfaction was assessed. The housing quality was evaluated using the Flemish Housing Code, and energy performance was calculated. A monitoring campaign in selected dwellings evaluated the IEQ. Interviews documented home-owners’ satisfaction. The results revealed a significant enhancement in housing quality, with post-renovation compliance reaching 83%. Energy performance notably improved, from a pre-renovation F-label prevalence (31% of the cases) to a post-renovation majority achieving a C-label (55%). The average indoor temperature in all rooms increased after renovation. A moderate correlation between enhancement in the living room and bathroom temperature and budget for energy performance measures was noted. The CO2 concentration in the majority of the homes remained unchanged. A total of 61% of the participants reported increased satisfaction with their dwelling post-renovation, with more pronounced improvement in winter. This enhanced satisfaction was correlated with improved energy performance.